Perlindungan Hukum Terhadap Konsumen Yang Dirugikan Dalam Transaksi Jual Beli Barang di Online Shop - Aldi Rozzaq Bimantara; Edi Pranoto (PLEDOI (Jurnal Hukum dan Keadilan), 2023)
The use of electronic media to function as digital data in making agreements will have an impact on the performance of companies that carry out their activities using electronic media such as the internet, but agreements made via the internet do not mean they do not cause problems. This problem is with the development of crime that utilizes the internet network, namely the rise of fraud via the internet, especially in online transactions. The government's efforts to provide consumer protection have been reflected in the establishment of Law No. 6 of 19999 concerning Consumer Protection. Where it has been regulated regarding the rights and obligations of consumers. In addition, there are rights and obligations for the seller. Therefore the authors are interested in conducting research with the title "Legal Protection of Consumers who are disadvantaged in buying and selling transactions of goods at online shops". The formulation of this problem is How to Legal Protection Against Consumers Who Are Aggrieved in Buying and Selling Transactions through Shopee E-commerce according to Law Number 8 of 1999 concerning Consumer Protection and How is Shopee's policy in protecting consumers in transactions who are disadvantaged in buying and selling transactions. This study uses a normative juridical type with a qualitative descriptive analysis focusing on secondary data. Based on the results of the study, it can be concluded that Law Number 8 of 1999 concerning Consumer Protection Law has provided efforts to protect buying and selling transactions online, namely the inclusion of rights and obligations owned by sellers and buyers that must be fulfilled. Concerning protection for online transactions at Shopee, Shopee also has various policies that refer to the provisions of Government Regulation (PP) number 80 of 2019 concerning Trading Through Electronic Systems (UU PMSE), namely Article 26 which contains the fulfillment of obligations for business actors and Article 27 which contains the provision of compliant services. The form of legal protection provided to consumers is particularly related to forms of loss such as default, unilateral cancellation, and Shopee account breaches.